Protecting vulnerable subjects in clinical research: children, pregnant women, prisoners, and employees. - Schwenzer KJ (Respiratory Care, 2008)
The federal has established guidelines ane regulations for the protection of vulnerable research subjects, especially children, pregnant women, cognitively impaired persons, and prisoners. In addition, students, residents, and employees are recognized as special research populations. Clinical investigators need to be aware of and use these federal guidelines appropriately. This article provides practical guidance for respiratory therapists who conduct research with these patient populations and solutions to the barriers investigators commonly encounter when studying these patient populations.